Általános iskolai szegregáció Magyarországon az ezredforduló után - Gábor Kertesi; Gábor Kézdi (Hungarian Academy of Sciences, Institute of Economics, 2009)
– The paper looks at school segregation in Hungary by ethnicity (Roma versus non-Roma) and social disadvantage. We use comprehensive data from the National Assessment of Basic Competences from 2006. School segregation is measured at various levesl: by micro-regions, within towns and cities, and and within schools (between classes). The novelty of the analysis is in its comprehensive nature. Comparsons to the racial and ethnic segregation of the U.S. school system reveals lower segregation on average in Hungary. The relation of segregation indices to city size and the fraction of minority students is very similar, and segregation in Hungary is stronger after controling for those factors.
Keywords: J15; I20; 330; School segregation; Roma minority; disadvantaged students; Schule; Roma-Bevölkerung; Ethnische Diskriminierung; Studierende; Ungarn